Situaciones de vulnerabilidad y estrategias resilientes de un grupo de padres de hijos con Trastorno del Espectro Autista (TEA) - Amaya, Alfa Celene Rea; Tomasini, Guadalupe Acle (Revista Cocar, 2017)
" Si un menor nace con una discapacidad ocurre un impacto en la familia que la coloca en situaciones de vulnerabilidad. El estudio de la resiliencia no es simple, los factores de riesgo y protección interactúan de forma dinámica, un factor de riesgo se puede convertir en un factor de protección ante la adversidad. El propósito del estudio es analizar las estrategias resilientes de padres y madres de niÃ±os con Trastornos del Espectro Autista (TEA) en conjunción con los procesos de transición de sus hijos. Es un estudio de caso situacional mediante la triangulación de la información de un grupo focal y una escala de habilidades para niÃ±os con TEA. Participaron tres madres, dos padres y una abuela de niÃ±os con TEA. Los hallazgos muestran el dinamismo del constructo de resiliencia, ya que los padres presentaron factores tanto de vulnerabilidad como estrategias resilientes para afrontar el TEA de su hijo. " Palabras clave: Resiliencia. Trastorno del espectro autista (TEA). Padres de hijos TEA. " " Vulnerability situations and resilient strategies of a group of parents of children with Autism Spectrum Disorder (ASD) " " Abstract " If a child is born with a disability, there is a great impact in his or her family in a way that place them into vulnerable situations. The study of resilience is not a simple one, because risk and protection factors interact in a dynamic way, a risk factor can turn into a protection factor when adversity occurs. The aim of the study is to analyze the resilient strategies applied by parents of children with Autism Spectrum Disorder (ASD) in conjunction with the transition processes of their offspringâ€™s. It is a study of a situational case performed by triangulating data on a focus group and the ASD Children Skills Scale. The participants were three mothers, two fathers and a grandmother of ASD children. The results show the dynamics of the resilience construct when participants are in vulnerability situations, they can manifest risk factors as affliction, stress and evasion behaviors as well as resilience strategies to cope with their childrenâ€™s ASD. " Keywords: Resilience. Autism spectrum disorder (ASD). Parents of ASDs. " " " " " " " " "